Knowledge of Antimicrobial Drug Resistance (AMR) Among Patients in a General Outpatient Clinic in Abuja Municipal Area Council (AMAC), Federal Capital Territory, Nigeria - Idoko, Lucy O.; Okafor, Kingsley C.; Lolo, Nomsu S. (British Journal of Healthcare and Medical Research, 2023)
Background: Antimicrobial resistance (AMR) is currently prevalent and has the potential to affect everyone, of any age, in any country. In humans, animals, and the environment, antimicrobial-resistant microbes are quickly emerging and spreading. This study aims to assess the knowledge of Antimicrobial Drug Resistance (AMR) among patients in a General Outpatient Clinic in Abuja Municipal Area Council (AMAC), Federal Capital Territory, Nigeria. Methods: This was a descriptive cross-sectional study among 400 clients in district hospital done in 2022. A multistage sampling technique was adopted for this study. Data was collected using self-administered structured questionnaire and analyzed and presented as tables, proportions, and percentages using the IBM SPSS 28 (Statistical Package for the Social Sciences) computer software (IBM SPSS Inc. 2021) Ethical approval was granted by Bingham University Teaching Hospital Ethical Research Committee, Jos, Plateau State. Results: The study revealed that the knowledge of antimicrobial resistance between male and female respondents. 8.5% of female respondents had good knowledge, 20.75% had fair knowledge while 27.75% had poor knowledge. Of all the male respondents, 8.5% had good knowledge, 13% had fair knowledge and 21.5% had poor knowledge. Summarily, only 68 (17.0%) of participants had good knowledge of antimicrobial resistance, 135 (33.75%) had fair knowledge of antimicrobial resistance, while 197 (49.25%) had poor knowledge of antimicrobial resistance. Test of association between knowledge of antimicrobial resistance and Sociodemographic showed that Marital Status (χ² (2, N=400) = 44.28, p < 0.045), Education (χ² (2, N=400) = 123.80, p < 0.001) and Age (χ² (2, N=400) = 112.95, p < 0.001) were statistically significant. Conclusion: The Federal, State, and Local governments, health care providers, and community health workers should focus on increasing awareness of AMR risk factors through health campaigns and program that will aid behavioural change.